Evaluation of structure–activity relationships of ginsenosides against amyloid β induced pathological behaviours in transgenic Caenorhabditis elegans. Issue 64 (16th August 2017) - Zhang, Mu; Qian, Fei; Liu, Qingling; Qian, Cheng; Thu, Pyone Myat; Wang, Yanyan; Zheng, Zu-Guo; Yang, Hua; Li, Ping; Xu, Xiaojun
Abstract : The systematic in vivo study comparing the effects of different ginsenosides on Aβ induced toxicity and cognitive impairment. Abstract : Amyloid β (Aβ) induced toxicity has been postulated to initiate synaptic loss and subsequent neuronal degeneration in Alzheimer's disease (AD). The activities of ginsenosides against AD are widely reported, however, a systematic in vivo study comparing the effects of different ginsenosides on Aβ induced toxicity and cognitive impairment has not been described. In addition, the correlation between molecular structures and their anti-Aβ activities remains uncovered. In the present study, the in vivo anti-Aβ effects of 17 ginsenosides were explored using three transgenic Caenorhabditis elegans ( C. elegans ) models that exhibits pathological behaviors associated with Aβ. We found that (1) ginsenoside Rc, Rd, 20( S )-Rg3, Compound K (CK) and Rg1 could significantly reduce Aβ deposits, (2) ginsenoside Rc, Rd, CK, Rk3 and Rg1 inhibit Aβ induced paralysis, and (3) ginsenosides 20( S )-Rg3, CK and Rk3 prevented Aβ induced defects in associative learning capacity and showed antioxidative activity both in vitro and in vivo . The structure–activity relationships of 17 ginsenosides were investigated by comparing their anti-Aβ effects in C. elegans models. Results showed that the protopanaxadiol-type has higher activities than the protopanaxatriol-type or oleanane-type; the anti-Aβ effects of ginsenosides are inversely related to the sugar numbers. The results of the present study gain insight into the in vivo protective effects of ginsenosides against Aβ induced toxicity, and provide useful information for the clinical use of ginsenosides.